Microvascular dysfunction determines infarct characteristics in patients with reperfused ST-segment elevation myocardial infarction: The MICROcirculation in Acute Myocardial Infarction (MICRO-AMI) study - McAlindon, Elisa (PLoS One, 2018)
BACKGROUND: In patients with reperfused ST-elevation myocardial infarction (STEMI) both invasive and non-invasive assessments of microvascular dysfunction, the index of microcirculatory resistance (IMR), and microvascular obstruction (MVO) by cardiovascular magnetic resonance (CMR), independently predict poor long-term outcomes. AIMS: The aims of this study were to investigate whether an invasive parameter (IMR), assessed at the time of primary percutaneous intervention (PPCI), could predict the extent of MVO in proportion to infarct size (MVO index). METHODS: 50 patients presenting with STEMI and TIMI flow ≤ I in the infarct related artery were prospectively recruited to the study, before undergoing PPCI. All patients underwent invasive IMR assessment at maximal hyperaemia using adenosine, and following stent insertion. CMR was performed on day 2 following STEMI, MVO was assessed both on first-pass rest perfusion (early MVO) and in the late gadolinium enhancement (LGE) images (late MVO) along with infarct size. The MVO index was calculated as the ratio of late MVO/infarct size. Differences between IMR quartiles and the MVO index were investigated. RESULTS: The median IMR was 38.5 (range 9 to 202). The median size of late MVO was 1.9% LV (range 0 to 21.0% LV). IMR predicted late MVO (p<0.01) and as IMR increased, the MVO index increased (r = 0.70, [95% CI 0.53, 0.82], p<0.001). An IMR cut-off of 40 significantly predicted the presence of late MVO on CMR (p<0.001). CONCLUSION: IMR measured at the time of PPCI in acutely reperfused STEMI is associated with the presence and severity of infarct damage as measured by the MVO index. TRIAL REGISTRATION: The Microcirculation in Acute Myocardial Infarction (MICRO-AMI). Clinicaltrials.gov NCT01552564. Registered 9th March 2012.